Cultural and creative industries development on cities: a perspective from urban innovation ecosystems - Yue Dong; Qingfeng Zhang (Environmental Research Communications)
As an emerging economic form, the cultural and creative industries (CCI) have gradually become a key force in driving urban economic transformation and enhancing urban competitiveness. In the knowledge economy, the CCI are producers of cultural content and vital sources of innovative resources. This study explores CCI’s role within urban innovation ecosystems and their impact on cities. The research employs a combination of theoretical model construction and empirical analysis. It begins with a literature review and theoretical analysis to construct a relationship model between the CCI and urban innovation ecosystems, as well as a hypothetical model of the impact of the CCI on cities. An online survey was conducted to collect data, and the results validate the models’ effectiveness. The findings indicate that the CCI significantly promotes urban development. They directly drive the economic transformation and upgrading of cities and indirectly foster sustainable urban development by optimizing the innovation environment and enhancing the vitality of innovation entities. The CCI plays a crucial role in urban innovation ecosystems, enhancing urban innovation capacity and competitiveness through interactions. The system reveals the pathways through which the CCI functions within urban innovation ecosystems and offers corresponding development recommendations. It provides theoretical support and practical references for promoting the synergy between the CCI and urban development.